Analysis of The Effect of Promotional Costs, and Third Party Funds on Financing BPRS Sarana Prima Mandiri Bangkalan Branch - Wahyuningsih, Riska; Rohman, Abdur; Amir, Faizal (MALIA: Journal of Islamic Banking and Finance, 2024)
Promotions and Third Party Funds are important aspects for increasing financing, This study discusses the influence of promotion costs, and third-party funds (DPK) on BPRS Sarana Prima Mandiri. The purpose is to observe and find out empirically the influence of promotional costs, and third-party funds on Financing at BPRS Sarana Prima Mandiri. This study is a quantitative research using time series data with the Vector Error Correction Model (VECM) approach. The data analysis technique in this study uses observation and sampling techniques which are carried out by taking data on promotion costs, and deposits from 2014 to 2022 (108 months). The results of the study show that promotional costs and third-party funds each have a significant negative effect on financing